Sociodemographic Risk Factors and Patterns of Medicolegal Injuries in a Tertiary Care Hospital: A Cross-Sectional Public Health Analysis: Sociodemographic Patterns in Medicolegal Injuries - Muhammad Arsalan Khan; Nasir, Mehreen; Zunaira Amin; Afshan Shahid; Samra Munawar (Journal of University College of Medicine and Dentistry, 2025)
Objective: To identify sociodemographic and injury-related risk factors associated with medicolegal cases reported at a tertiary care hospital in Lahore, Pakistan, and to explore their implications for preventive public health strategies. Methodology: This cross-sectional study was conducted from June to December 2024 at the Services Institute of Medical Sciences, Lahore. Data from 370 medicolegal cases were extracted using non-probability consecutive sampling from the institutional medico-legal register. A structured questionnaire collected demographic characteristics and injury-related variables. Data were analyzed using SPSS v29, with chi-square tests used to assess associations between employment status and injury characteristics. A p-value <0.05 was considered statistically significant. Results: Among the 370 cases, the majority were male (68.1%), under 45 years of age (81.1%), from urban areas (93.8%), and worked as unskilled labourers (44.9%). Intentional injuries comprised 72.7% of cases, with physical assault being the most common mode (75.4%) and the head and neck the most frequently affected site (53.5%). Employment status was significantly associated with the nature of injury: employed individuals experienced more accidental injuries (29.3%), while unemployed individuals had a higher prevalence of intentional injuries (86%). Conclusion: Medicolegal injuries disproportionately affect younger males and unskilled workers, with intentional physical assaults being the predominant cause. A public health approach emphasizing injury surveillance, occupational health interventions, and violence prevention strategies is essential to mitigate the burden of such injuries.